Risk factors for Mycoplasma genitalium infection among female sex workers: a cross-sectional study in two cities in southwest China - Xiang Zhi; Yin Yue-Ping; Shi Mei-Qin; Jiang Ning; Han Yan; Wang Hong-Chun; Zheng Bing-Jie; Liang Guo-Jun; Chen Xiang-Sheng (BMC Public Health, 2012)
Abstract Background Mycoplasma genitalium (MG) is one of the common causes of non-gonococcal urethritis (NGU) in men and is associated with cervicitis, endometritis, and pelvic inflammatory diseases (PID) in women. The prevalence of MG infection has been reported to be high among female sex workers (FSWs) in many countries, but limited information is known among this population in China. Methods From July to September 2009, venue-based FSWs were recruited in two cities (Wuzhou and Hezhou) of Guangxi Autonomous Region in southwest China. Information of socio-demographic and behavioral characteristics was collected by a questionnaire-based interview. Cervical specimens were obtained for detection of MG using a real-time polymerase chain reaction (PCR) assay targeting mgpA gene. Results The overall prevalence of MG infection among 810 FSWs was 13.2% (95% CI = 10.87%–15.52%). MG infection was significantly associated with less education (adjusted odds ratio (AOR) = 2.36, 95% CI = 1.15–4.87) consisting of junior high school or below, being single (AOR = 2.27, 95% CI = 1.42–3.62), migrant background (AOR = 2.03, 95% CI = 1.29–3.20), and absence of any STI symptoms in the previous year (AOR = 1.66, 95% CI = 1.09–2.52). Conclusions MG infection was prevalent among FSWs in the study areas. This pattern of infection suggests that an increasing attention should be paid to MG screening and treatment in this high risk population.